Management of image formation of a higher medical education institution - Shalimova , I.; Shalimova , A. (Problems of Engineer-Pedagogical Education, 2023)
Based on a study of psychological and pedagogical literature on the management of higher education institutions, a comparative analysis of the concept "image of an organization" in the works of various authors was conducted, and the most acceptable one in terms of improving the management of a higher medical education institution was selected. The article clarifies that the content of the process of image management of a higher education institution is the formation (maintenance) of the image of a medical university, which corresponds to its development strategy, and the creation of effective communication with target audiences. The article examines the factors influencing the image of an institution of higher medical education and identifies key elements, the management of which allows ensuring the desired image of the university in the minds of the most important target audiences. The article analyzes the existing process of image management of the state institution of higher education Kharkiv National Medical University (KhNMU), and the distribution of functional responsibilities among top managers of the institution. The article substantiates the expediency of expanding the options for promoting educational services of KhNMU through the use of traditional (advertising, Internet marketing and exhibition activities) and innovative (event marketing, use of social networks and messengers, viral marketing) methods. A comprehensive analysis of the image of the institution of higher medical education revealed a number of problems with the image management process at KhNMU. Therefore, the authors of the article consider it expedient to pay attention to improving the level of image formation and to develop an appropriate complex targeted program at Kharkiv National Medical University.